Emerging Organic Pollutants in Waste Waters and Sludge - Barceló, Damià; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Over the past fifteen years regulatory agencies have relied on their approaches to characterise and control the release of toxic substances into the aquatic environment: a GC/MS analysis for U.S. EPA designated 126 priority pollutants and 132 dangerous substances according to the European 76/464/CEE Directive and on the bioassays with aquatic bioorganisms. "Emerging Contaminants" correspond in most cases to irregulated contaminants, e.g. surfactants, pharmaceuticals and personal care products (PPCP), or gasoline additives. These two volumes, 5/I and 5/O, of this Handbook deal with the analytical, toxicological and environmental issues of these toxicants. Based on results of up-to-date research they give the reader a balanced view on this rapidly developing and complex subject.
Marina Kuster, Maria López de Alda, and Damià Barceló: Estrogens and Progestogens in Waste Water, Sludge Sediments and Soil -- A. Rigol, A. Latorre, S.Lacorte, and D. Barceló: Toxic Compounds in Paper Mill Wastewaters -- M.D. Hernando, I. Ferrer, A. Agüera, and Amadeo R. Fernandez-Alba: Evaluation of Pesticides in Wastewaters. A Combined (Chemical and Biological) Analytical Approach -- Staci L. Simonich: Fragance Materials in Wastewater Treatment -- M.-Carmen Estévez, Héctor Font, Mikaela Nichikova, J.-Pablo Salvador, Begona Varela, Francisco Sánchez-Baeza, and M.-Pilar Marco: Immunochemical Determination of Industrial Emerging Pollutants -- M.-Carmen Estévez, Héctor Font, Mikaela Nichikova, J.-Pablo Salvador, Begona Varela, Francisco Sánchez-Baeza, and M.-Pilar Marco: Immunochemical Determination of Pharmaceutical and Personal Care Products as Emerging Pollutants -- Olivier Thomas, and Marie-Florence Pouet: Wastewater Quality Monitoring: On Line/On Site Measurement.
Keywords: Water pollution; Water quality; Environmental management; Environmental pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Quality/Water Pollution; Environmental Management; Terrestrial Pollution